Determining the efficacy of disinfectants at nucleic acid degradation - Kirsty Meldrum (Journal of Applied Microbiology, 2023)
AimsNucleic acids, particularly antibiotic resistance genes, are commonly found on surfaces within healthcare environments, with levels not reducing following cleaning. Within the UK, there are no regulations for testing disinfectants against nucleic acids.Methods and resultsA series of commonplace in vitro methods were used to determine disinfectant-induced physical and functional damage to various nucleic acids; RNA (10 μg), genomic DNA (2 μg), and plasmids (1 μg). Using these methods, the optimal residence time (10 minutes) and working concentration (10%) were determined for a new disinfectant. Furthermore, comparison of disinfectants with different active ingredients including lactic acid (LA), sodium hydroxide (NaOH), chloroxylenol (PCMX), and quaternary ammonium compounds (QACs), were compared to controls. All disinfectants showed greater degradation by gel electrophoresis of genomic DNA and RNA than of purified plasmids. Functional analysis using quantitative polymerase chain reaction (qPCR) and polymerase chain reaction (PCR) demonstrated that no disinfectant tested (apart from control) could damage DNA to the level where PCR amplification was not possible, and only the NaOH reagent could achieve this for RNA.ConclusionsThe set of methods described herein provides a platform for future standardization and potential regulation regarding monitoring cleaning solutions for their activity against nucleic acids.